Redescription of the chaetotaxy of the fourth instar larva of Lutzomyia evansi (Diptera: Psychodidae: Phlebotominae) - CAZORLA, DALMIRO; OVIEDO, MILAGROS; VÍVENES, MARÍA ALEJANDRA (Revista Colombiana de Entomología, 2010)
The chaetotaxy of fourth instar larvae of Lutzomyia evansi, obtained from laboratory conditions, is redescribed and illustrated. Measurements of the setae are also provided. The comparative morphological study suggests that fourth instar larvae of L. evansi, as well as the other species of the verrucarum series, can be placed in Group 4 of the neotropical phlebotomine which posses antennae with a short basal segment and an ovoid distal segment, which seems to support the correct proposed groupings based on characters of the imagos. The significance of the importance to standardize the nomenclature of sand fly chaetotaxy and use of a single chaetotaxy system for their description is discussed.